PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VIII SMPN SATU ATAP MESI - Honorata Melania Nawas; Ainun Jariyah; Yosephina Payu Wao (Jurnal Bionatural, 2025)
The discovery learning model encourages students to find their own knowledge about something. This research aims to determine the effect of the discovery learning model on the learning outcomes of class VIII students at SMPN Satu Atap Mesi. The type of research is quantitative descriptive with a pre-experiment one group pretest-posttest design.  The population in this study was 50 students consisting of two classes, namely class VIIIA and class VIIIB. The sample in this study was 25 class VIII students obtained using random sampling techniques. The data obtained from the research sample is in the form of learning outcomes in cognitive aspects. Data analysis was carried out using the t test. The results of the research showed that the average score for students' posttest learning outcomes in the cognitive domain was 86.40. Based on the results of hypothesis testing using one sample t-test analysis, the sig (2-tailed) value is 0.000 < 0.05, which indicates that the discovery learning model is effective in improving student learning outcomes